Molecular interaction of artemisinin with translationally controlled tumor protein (TCTP) of Plasmodium falciparum - Eichhorn, Tolga; Winter, Dominic; Büchele, Berthold; Dirdjaja, Natalie; Frank, Martin; Lehmann, Wolf-Dieter; Mertens, Rolf; Krauth-Siegel, Renate; Simmet, Thomas; Granzin, Joachim; Efferth, Thomas (Biochemical pharmacology, 2013)
Malaria causes millions of death cases per year. Since Plasmodium falciparum rapidly develops drug resistance, it is of high importance to investigate potential drug targets which may lead to novel rational therapy approaches. Here we report on the interaction of translationally controlled tumor protein of P. falciparum (PfTCTP) with the anti-malarial drug artemisinin. Furthermore, we investigated the crystal structure of PfTCTP. Using mass spectrometry, bioinformatic approaches and surface plasmon resonance spectroscopy, we identified novel binding sites of artemisinin which are in direct neighborhood to amino acids 19-46, 108-134 and 140-163. The regions covered by these residues are known to be functionally important for TCTP function. We conclude that interaction of artemisinin with TCTP may be at least in part explain the antimalarial activity of artemisinin.